2018
DOI: 10.1097/ta.0000000000001945
|View full text |Cite
|
Sign up to set email alerts
|

EAST Multicenter Trial on targeted temperature management for hanging-induced cardiac arrest

Abstract: Therapeutic study, level IV; prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…Classification and Regression Tree is a form of machine learning that uses a given set of variables to create validated hierarchical decision trees, which has been applied in a range of disciplines, including in studies of trauma patients. [15][16][17] This method was chosen given its utility in determining both variable importance and the optimal cutoff values for each variable for predicting outcome. 15 To determine optimal splits in our predictor variables, the Gini coefficient was used, and cost complexity pruning was performed to prevent overfitting and build the most efficient decision tree.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Classification and Regression Tree is a form of machine learning that uses a given set of variables to create validated hierarchical decision trees, which has been applied in a range of disciplines, including in studies of trauma patients. [15][16][17] This method was chosen given its utility in determining both variable importance and the optimal cutoff values for each variable for predicting outcome. 15 To determine optimal splits in our predictor variables, the Gini coefficient was used, and cost complexity pruning was performed to prevent overfitting and build the most efficient decision tree.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, recent studies reported that TTM was not associated with favorable neurological outcomes in patients with PCAS by hanging 12 . A multicenter retrospective study reported that TTM worsened the unadjusted survival and neurological outcomes; however, the possibility of selection bias was suggested 13 . To date, no randomized control trials have been conducted on TTM in patients with PCAS by hanging.…”
Section: Discussionmentioning
confidence: 99%
“…Factors similar to those affecting the risk of cardiac arrest may be involved in the substantial variability in reported hospital mortality rates, from about 10% to almost 80% 12,[16][17][18] . This variability contrasts sharply with the finding in most studies that about 10% of survivors had residual neurological impairments responsible for dependency 10,11,13,14,16,19 .…”
Section: Discussionmentioning
confidence: 99%
“…4 Importantly, cerebral anoxia may be related to cardiac arrest and/or to compression of the cervical blood vessels during hanging. 4,14 Cerebral imaging studies, when performed, have shown oedema, ischemia 10,13,[17][18][19][20][21] , and subarachnoid bleeding from cervical arteries. Subdural haematoma has been found in nearly one fourth of patients and usually ascribed to a head injury sustained during unhanging 17 .…”
Section: Discussionmentioning
confidence: 99%